2019
DOI: 10.5812/numonthly.96628
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc Level in Recurrent Nephrotic Syndrome

Abstract: Background: Based on the evidence, the correction of zinc deficiency in patients with nephrotic syndrome may improve the prognosis of these patients. Objectives: So this study aimed to investigate the serum zinc level in children with nephrotic syndrome. Methods: This cross-sectional study was conducted in 102 children with nephrotic syndrome. After obtaining informed consent, we collected data regarding age, gender, the severity of nephrotic syndrome (mild, moderate, and severe), and serum zinc level. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 7 publications
(7 reference statements)
0
8
0
Order By: Relevance
“… 19 Other studies documented the participants’ mean ages as 6.38 ± 3.42 years, 25 6.5 ± 3.7 years, 26 and 6.2 ± 3.2 years. 27 The majority of the studies reported male predominance 18 , 24–28 while one study showed a female predominance. 16…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“… 19 Other studies documented the participants’ mean ages as 6.38 ± 3.42 years, 25 6.5 ± 3.7 years, 26 and 6.2 ± 3.2 years. 27 The majority of the studies reported male predominance 18 , 24–28 while one study showed a female predominance. 16…”
Section: Resultsmentioning
confidence: 98%
“… 27 The majority of the studies reported male predominance 18 , 24–28 while one study showed a female predominance. 16…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations